Letter to Chancellor Glenn S. Dumke, California State University and Colleges from Assemblyman J.K. (Ken) MacDonald - J.K. (Ken) MacDonald:::::: (1976)
In a May 13, 1976 letter, Assemblyman J. K. (Ken) MacDonald wrote to Chancellor Glenn S. Dumke regarding postsecondary education planning in Ventura County. He explained that he had been working with local officials to explore innovative approaches to better serve current and future higher education needs. Although he supported the administration's proposal to sell the state college site in Ventura County, he was committed to using the proceeds to promote a joint effort with Oxnard Community College. MacDonald requested assistance in arranging a meeting in Ventura County to further discuss the proposal.